Rigorous design of multiphase reactors: Identification of optimal conditions for mass transfer limited reactions - Xie, Mingquan; Freund, Hannsjörg (Chemical engineering and processing, 2018)
[Display omitted] •Dynamic optimization approach for multiphase reactor design.•Potential heat and mass fluxes which are not technically limited are optimized.•Sensitivity analysis regarding limited fluxes performed under optimal conditions.•A novel 2D model for chemical absorption of CO2 is established and validated.•Optimal temperature profiles are identified for chemical absorption of CO2. Multiphase reaction systems are often complex due to the interaction of reaction and transport processes. To design optimal reactors for such systems, a rigorous optimization is necessary. In this regard, this work proposes extensions of a reactor design methodology based on rigorous optimization. Each phase is represented by one fluid element, subject to different mass and energy fluxes. While the unlimited external fluxes are optimally provided along the reaction route, sensitivity analysis of the parameters related to the limited external fluxes is performed. The extended methodology is applied in the reactor design for chemical absorption of CO2 as an example for complex multiphase reaction systems with severe mass transfer limitation. An accurate model which is also numerically suitable for optimization has been set up and validated with pilot plant data from literature. Optimal temperature profiles which result from balancing the different temperature-dependent phenomena are identified for cases with different inlet conditions, and tailor-made heat control strategies are shown for these cases. The potential of the developments in improving mass transfer rates by, e.g., structural design or solvent design has been quantified. This model-based design methodology is generally applicable to different multiphase reaction systems with severe mass transfer limitation.